2011
DOI: 10.1007/s00726-011-0929-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic differentiation of amniotic fluid stem cells

Abstract: In 2003, human amniotic fluid has been shown to contain stem cells expressing Oct-4, a marker for pluripotency. This finding initiated a rapidly growing and very promising new stem cell research field. Since then, amniotic fluid stem (AFS) cells have been demonstrated to harbour the potential to differentiate into any of the three germ layers and to form three-dimensional aggregates, so-called embryoid bodies, known as the principal step in the differentiation of pluripotent stem cells. Marker selection and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Many research groups have found that AFSCs are highly neurogenic which can be a good candidate for neuronal regenerative purposes (Prusa et al, 2004;Rosner et al, 2012). However, no study has investigated the effect of monolayer differentiation on AFSCs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many research groups have found that AFSCs are highly neurogenic which can be a good candidate for neuronal regenerative purposes (Prusa et al, 2004;Rosner et al, 2012). However, no study has investigated the effect of monolayer differentiation on AFSCs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Stem cells in amniotic fluid are of fetal origin but the in vivo function of AFS cells in amniotic fluid is still unclear (Rosner et al 2011). Importantly, it remains to be explored whether pluripotent AFS cells are limited in their differentiation potential in a way that has been already described for murine neural stem cells exposed to a very low MeHg concentration (0.0025 lM).…”
Section: Effects Of Mehg On Cell Number and Cell Size Of Afs Cellsmentioning
confidence: 99%
“…Similar findings were reported for human embryonic stem cells (hESC), i.e., MeHg seems to inhibit hESC neuronal precursor differentiation by mechanisms different from general cytotoxicity and the differentiation of neuronal precursor-like cells is more sensitive to MeHg exposure than their maturation into neuron-like cells (Stummann et al 2009). This might be highly relevant also for AFS cells that harbor the potential to differentiate into neurogenic, osteogenic, chondrogenic, adipogenic, hepatic, myogenic, renal, and hematopoietic lineages (Rosner et al 2011). …”
Section: Effects Of Mehg On Cell Number and Cell Size Of Afs Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both inhibitors block p70 S6K1 kinase activity to phosphorylate S6 without affecting the S6 nucleocytoplasmic distribution, but, whereas rapamycin inhibits p70 S6K1 T389 phosphorylation and thus nuclear localization, PF-4708671 strongly induces p70 S6K1 T389 phosphorylation and nuclear localization. 12 Since different mTOR/S6K inhibitors can mediate such different, even opposite, effects on the spatial regulation of their targets, which themselves again have distinct cytoplasmic and nuclear substrates, we want to point out that it is of intriguing relevance for their therapeutic usage to provide a detailed molecular investigation of the tumor, including the spatial regulation of both the drug targets and their substrates, causatively involved in the transformation process. The hypothesis is that the usage of such inhibitors could, for example, block substrate A but could simultaneously trigger spatial deregulation of substrate B, which might have adverse effects, even tumor-promoting consequences.…”
Section: Spatial Consequences Of Blocking Mtor/s6kmentioning
confidence: 99%